2021
DOI: 10.1139/cjm-2020-0146
|View full text |Cite
|
Sign up to set email alerts
|

Rates of fluoroquinolone resistance in domestically acquiredCampylobacter jejuniare increasing in people living within a model study location in Canada

Abstract: Antimicrobial resistance was evaluated in Campylobacter jejuni isolated from 1,291 diarrheic people over a 15 year period (2004-2018) in Southwestern Alberta, a model location in Canada with a high rate of campylobacteriosis. The prevalence of resistance to chloramphenicol, clindamycin, erythromycin, and gentamicin was low during the examination period (≤4.8%). Resistance to tetracycline remained consistently high (41.6-65.1%), and resistance was primarily conferred by plasmid-borne tetO (96.2%). Resistance ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…Antibiotic treatment is usually only given to patients exhibiting severe forms of the disease, or to high-risk individuals (e.g., neonates, pregnant women, and immunocompromised individuals) ( Yang et al, 2019 ). For Campylobacter spp., there are increasing rates of fluoroquinolone resistance, specifically, ciprofloxacin resistance being observed in many countries throughout the world ( World Health Organization, 2017a , b ), including Canada ( Inglis et al, 2021 ). In Canada, ciprofloxacin is classified as an antibiotic of “very high importance” by Health Canada, and it is one of the most prescribed antibiotics for the treatment of campylobacteriosis ( Agunos et al, 2013 ; Inglis et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibiotic treatment is usually only given to patients exhibiting severe forms of the disease, or to high-risk individuals (e.g., neonates, pregnant women, and immunocompromised individuals) ( Yang et al, 2019 ). For Campylobacter spp., there are increasing rates of fluoroquinolone resistance, specifically, ciprofloxacin resistance being observed in many countries throughout the world ( World Health Organization, 2017a , b ), including Canada ( Inglis et al, 2021 ). In Canada, ciprofloxacin is classified as an antibiotic of “very high importance” by Health Canada, and it is one of the most prescribed antibiotics for the treatment of campylobacteriosis ( Agunos et al, 2013 ; Inglis et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For Campylobacter spp., there are increasing rates of fluoroquinolone resistance, specifically, ciprofloxacin resistance being observed in many countries throughout the world ( World Health Organization, 2017a , b ), including Canada ( Inglis et al, 2021 ). In Canada, ciprofloxacin is classified as an antibiotic of “very high importance” by Health Canada, and it is one of the most prescribed antibiotics for the treatment of campylobacteriosis ( Agunos et al, 2013 ; Inglis et al, 2020 ). The reason for an increasing prevalence of fluoroquinolone resistance is not known; however, with more extensive surveillance of AMR in Campylobacter , potential routes of transmission could become more apparent [reviewed in Sproston et al (2018) ].…”
Section: Introductionmentioning
confidence: 99%
“…We concurrently contrasted subtypes of C. jejuni in water with those from diarrheic people over a 1-year period within a model location in an attempt to resolve the extent to which waterborne C. jejuni contribute to campylobacteriosis. It is noteworthy that SWA was chosen as a model location because: (i) there are high rates campylobacteriosis; (ii) people living in rural locations make up a significant proportion of individuals living in the region (0.7:1 rural:urban ratio); (iii) the human population is moderate in size (180,994 people in 2016); (iv) there is a single public diagnostic facility servicing the region; (v) the Oldman River is the primary watershed with a spatial gradation of human agricultural activity from west to east; (vi) there is a high density of livestock production with ≈2.7M poultry, ≈0.39M pigs, and ≈1.1M cattle with 51% being beef cattle in confined feeding operations (CFOs) (Alberta Government 2014); and (viii) intensive research targeting Campylobacter has been conducted in the region with extensive fingerprinted C. jejuni strains accessioned into the Canadian Campylobacter Comparative Genomic Fingerprinting database (C3GFdb) (Inglis et al 2021). Others have comparatively studied the molecular epidemiology of C. jejuni subtypes in water and people (Inglis et al 2019;Joensen et al 2018), but limited research to date has examined C. jejuni in water, wastewater, and people in the same space and time.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies conducted elsewhere have indicated waterfowl as a major source of C. jejuni in surface waters (Abulreesh et al 2006;Carter et al 2009; Van Dyke et al 2010), our results indicate that C. jejuni associated with cattle was a major contributor of the bacterium to water. Indeed, cattle have been implicated as a primary source of C. jejuni infecting people in SWA (Inglis et al 2019;Inglis et al 2021). However, findings from the current study indicate that water was not the primary direct mechanism by which C. jejuni are transmitted to people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation